Investigating secondary education teachers’ attitudes, knowledge, and perceptions toward the inclusive education of students with and without special educational needs - Kyriakou, Maria K.; Loizidou Ieridou, Nataly (Education Sciences, 2025)
This thesis thoroughly examines the attitudes, knowledge and perceptions of secondary school teachers regarding the inclusion of students with and without special educational needs in Cyprus. In the research, a quantitative investigation was carried out in a case study school as well as in Cyprus in order to collect the opinions of the teachers either those that they were employed in the school that was the case study, but also all around Cyprus too. At the same time, a quality control of opinions was implemented through interviews in the case study school with the School Principal, Assistant Principal in charge of Special Education, the Vocational Education Counselor and the Liaison Officer in order to collect more information and opinions for the inclusive education in public schools in Cyprus.